Cancer-Testis Antigens and Immunotherapy in the Light of Cancer Complexity. (4th March 2015) - Grizzi, F.; Mirandola, L.; Qehajaj, D.; Cobos, E.; Figueroa, J. A.; Chiriva-Internati, M.
Abstract : The ability of immunotherapy to evoke successful antitumor immune responses has been well documented over the past decade. Despite abundant preclinical data, it is only with the recent approval by the Food and Drug Administration (FDA) of the drugs such as sipuleucel-T and ipilimumab that immunotherapy is finally being recognized as a viable alternative to traditional therapies for treatment of various cancers. Despite the ability of immunotherapy to elicit successful antitumor immune responses, its efficacy is hindered by several factors. Among these are the paucity of tumor-associated antigens (TAA) that can be used as effective targets and the systemic toxicities that often lead to treatment interruption. Indeed, such adverse effects, which can be immunological and/or parenchymal, can be particularly severe and even fatal to some patients. A family of TAA called cancer-testis antigens (CTA) has been identified and their encoding genes have been extensively investigated. CTA expression has been demonstrated in a variety of human cancer tissues, and at least 19 CTA have been found to elicit humoral and/or cellular immune responses in cancer patients. Here we discuss how CTA and immunotherapy will most likely play a major role in the cure of cancer in the light of cancer complexity.